Evaluation of UHF transfer function in a power transformer for real-time partial discharge detection - Promwong, Sathaporn; Tiengthong, Thanadol (My University, 2020)
The UHF transfer function is significant for a short-range communication system, e.g., a real-time diagnosis of partial discharge (PD). Real-time diagnosis of the PD has become a challenging topic of improving the diagnosis of high voltage equipment, including a power transformer. Further, the PD detection in high voltage equipment is critical since the PD can cause severe damage to electrical systems. The PD detection methods are classified by a phenomenon of the PD. The PD detection by electromagnetic (EM) method is regulated by IEC TS 62478, which specified the UHF band for the PD detection in power transformers. Hence, an evaluation of frequency characteristics is essential to achieve an excellent diagnostic performance. In this paper, a complex form of channel analysis is applied with the PD detection method. The measurement model in a power transformer is proposed. The optimum receiver is introduced to maximize SNR and hence it is easy to analyze the results. The results were analyzed by using magnitude, phase, group delay, received waveform, and path loss parameters. The results show that the measured channel is affected by the structure of the power transformer. The contribution of this research is useful for improving the precision of the PD detection with EM method and building an accurate real-time partial diagnosis via a smartphone or laptop computer.
Keywords: Complex form; Friis’ transmission formula; Partial discharge; UHF; UHF transfer function